Corporate Social Responsibility of Natura Brasil - Schneeweissová, Adéla (2022)
In recent decades, pollution has been an ongoing problem around the world, with the cosmetics industry being no exception. This bachelor thesis explains CSR concept in relation to the cosmetics industry with a focus on the Brazilian brand Natura. The main goal of this thesis is to analyze the awareness of CSR in Brazil. The topics regarding the problems in cosmetics industry, world trends and the implementation of CSR are introduced in the theoretical part. The practical part consists of research, carried out in a qualitative and quantitative method, that provides with information on how aware consumers of Brazilian market are of CSR, if CSR has impact on their shopping behavior and what their attitudes towards sustainability are.